HOW ERRORS MADE IN ESSAY WRITING: AN ANALYSIS USING GRAMMARLY SOFTWARE IN EFL STUDENTS - Ismawati Ismawati; Erwin Akib; Arief Muhsin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Errors in writing are naturally made in EFL teaching. This research aimed to find out the errors of correctness, clarity, engagement, delivery, and plagiarism in student essay writing using Grammarly Software in the third semester of English education. This research conducted at Muhammadiyah University of Makassar. The researcher used the descriptive quantitative method. The participants were 21 students from the third semester at English education of University Muhammadiyah of Makassar. The study took sample by apply purposive sampling. The instrument of this research is the students’ essay writing. The research results found 452 errors based on Grammarly software made by the third semester in English education at University Muhammadiyah of Makassar. Those errors can classify as follow: 73.5% errors of correctness, 17.5% errors of clarity, 7.7 % errors of engagement, 1.3% errors of delivery, and 0% errors of plagiarism.